A comprehensive review of techniques for increasing the efficiency of evacuated tube solar collectors. Issue 4 (April 2023) - Aggarwal, Sorabh; Kumar, Raj; Lee, Daeho; Kumar, Sushil; Singh, Tej
Abstract: With the growing energy needs, a conscious effort has been made to use non-conventional energy sources to generate clean energy efficiently. Solar energy has always been popular among humanity. Using solar energy in heating applications is one of the most prominent ways to extract solar power. Various developments have been made to augment solar water heating system (SWHS) performance. Each modified design of SWHS has its advantages and disadvantages. Broadly, solar water heaters are categorized into two types: Flat plate solar collectors (FPSCs) and evacuated tube solar collectors (ETSCs). Earlier studies show that evacuated tube SWHS are more efficient than flat plate SWHS. Extensive research is going on the design modification of evacuated tube SWHS to enhance their efficiency. Firstly, the present review article briefly introduced the numerous types of solar collectors and their range of operation. The current work reviews various techniques used for heat transfer enhancement in SWHS, their advantages, and the region of applications. The article concentrates on research involving the usage of energy storage medium, nanomaterials, reflecting surfaces, and hybrid techniques for performance augmentation of ETSCs. Graphical abstract: Image 1